Perancangan Aplikasi Manajemen Hutang Usaha Mikro Kecil Menengah Berbasis Website - Latifah, Ayu; Mulyani, Asri; Burdani, Aditya Mauludin (Institut Teknologi Garut, 2024)
In the context of current business developments, technology plays a crucial role in supporting the operations of Usaha Mikro Kecil Menengah (UMKM). However, there are still many UMKM, including in Sukasenang Village, Garut Regency, which rely on manual systems in managing financial data, especially regarding debt recording which still uses risky handwritten methods. Obstacles in accounts payable and receivable management also appear, where recording errors and differences in calculations between customers, suppliers and employees often occur. In this context, this research aims to develop a web-based debt management application to provide an efficient solution for managing debt transactions accurately, reducing recording errors, and ensuring orderly data storage. The Rational Unified Process methodology was used in developing this application, involving the stages of Inception, Elaboration, Construction, and Transition, with alpha testing using the Black Box Testing method. The result is an effective application in managing UMKM debts and receivables, which is expected to make a valuable contribution to UMKM financial management, especially regarding managing business debts.